A Numerical Model for Railroad Freight Car-to-Car End Impact. (10th December 2012) - Chen, Chao; Han, Mei; Han, Yanhui
Abstract : A numerical model based on Lagrange-D'Alembert principle is proposed for car-to-car end impact in this paper. In the numerical model, the friction forces are treated by using local linearization model when solving the differential equations. A computer program has been developed for the numerical model based on Runge-Kutta fourth-order method. The results are compared with the Multibody Dynamics/Kinematics software SIMPACK results and they are close. The ladings' relative displacement to struck car and the relative displacement between two ladings get larger as impact speed increases. There is no displacement between two ladings when the contact surfaces have the same friction coefficient.